Congenital hemophilia A diagnosed with postoperative hemorrhage after thyroidectomy for papillary thyroid carcinoma: a case report - Marie Saitou; Muneo Okamoto; Ryuta Nagaoka; Tomoo Jikuzono; Masaomi Sen; Hiroko Kazusaka; Mami Matsui; Iwao Sugitani (Surgical Case Reports)
Abstract Background Postoperative bleeding in thyroid surgery is a serious complication with fatal outcomes. Risk factors for postoperative hemorrhage have been reported as old age, male sex, Graves' disease, use of anticoagulants, and hematological disorders. Among the hematological diseases, congenital hemophilia is an inherited bleeding disorder characterized by absence or reduced levels of clotting factors VIII or IX. Most patients with hemophilia display bleeding symptoms during infancy or childhood, but diagnosis could be delayed in mild cases. We report a case of congenital hemophilia A that was diagnosed after three episodes of postoperative bleeding after thyroid surgery. Case presentation A 46-year-old man developed repeated postoperative hemorrhage after thyroid surgery for thyroid cancer. In this case, several irregularities were seen in the postoperative course, such as a relatively long interval between surgery and bleeding, the lack of an obvious bleeding point, fresh red blood dripping from the drain insertion site on the second postoperative day, and repeated bleeding three times. We therefore considered that the cause of postoperative hemorrhage might be other than the surgical operations. After a thorough examination, hemophilia A was diagnosed. Conclusions Hemophilia is a risk factor for postoperative bleeding in thyroid surgery. However, mild hemophilia shows normal prothrombin time and activated partial thromboplastin time. We encountered a case of papillary thyroid carcinoma associated with congenital hemophilia A, which was diagnosed after repeated bleeding.